2008
DOI: 10.5380/ce.v13i1.11949
|View full text |Cite
|
Sign up to set email alerts
|

Estressores E Coping Vivenciados Por Enfermeiros Em Um Serviço De Atendimento Pré-Hospitalar

Abstract: Pesquisa realizada em um Serviço Pré-Hospitalar (SAMU) de Porto Alegre, em 2007. Objetivos: identificar estressores vivenciados por enfermeiros que atuam no SAMU, identificar estratégias de enfrentamento utilizadas para lidar com o estresse no ambiente de trabalho e as repercussões na assistência aos usuários. Participaram 15 enfermeiros e os dados foram coletados mediante o "Inventário de Estresse em Enfermeiros" e analisados com o SPSS-7.5 e estatística descritiva. Estressores: esforço físico, falta de mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 8 publications
0
23
0
7
Order By: Relevance
“…In this context, nurses require knowledge, effort and skills, (4)(5)(6)11) as well as rapid and effective decision-making (6). In this situation, stress arises as a complex and dynamic physiological and psychological response in the body, triggered when the individual is faced with stressors, which may produce physical and psychological diseases.Thus, occupational stress is determined by the perception of the professional about his/her work demands as stressors, and by his/her ability to face them (4)(5)(6)(8)(9)(10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this context, nurses require knowledge, effort and skills, (4)(5)(6)11) as well as rapid and effective decision-making (6). In this situation, stress arises as a complex and dynamic physiological and psychological response in the body, triggered when the individual is faced with stressors, which may produce physical and psychological diseases.Thus, occupational stress is determined by the perception of the professional about his/her work demands as stressors, and by his/her ability to face them (4)(5)(6)(8)(9)(10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that when faced with a stressor, the body experiences three phases: in the first, a phase of alarm or alert, the body identifies the stressor and activates the neuroendocrine system.The second phase, of adaptation or resistance, is the moment in which the body repairs damage caused by the alarm reaction and reduces hormonal levels.The third phase occurs if the stressor remains present, this is the phase of exhaustion, that comprises the onset of a disease associated with stress (1,7) . Therefore, it is important that nurses who work in an urgent and emergency care setting recognize the stressors in their work environments, and their repercussions on the health-disease process, and seek solutions to mitigate them and face them, preventing damage to their health and guaranteeing good care for their patients (6) . Knowledge of this process is relevant, however, it is considered that the meaning that professionals confer upon their work is a protective factor against illnesses.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations